Analysis Of Technical Efficiency And Production Risk Of Rice Farming In Tanah Sepenggal Sub-District, Bungo Regency. - Nainggolan, Saidin; Damayanti, Yusma; Veni, Marlina (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to determine: 1) The description and implementation of lowland rice farming in Tanah Sepenggal Subdistrict, 2) The effect of input use on actual and frontier production, and 3) The effect of input use on production risk. A descriptive analysis was used to provide a general overview, technical efficiency was analyzed using the Cobb-Douglas production model, and production risk was analyzed using the Just and Pope model. The research was conducted in the villages of Empelu, Teluk Pandak, and Sungai Gambir, which were selected using a simple random sampling method. The results showed that the use of production inputs such as urea fertilizer, NPK fertilizer, and land area had a significant effect on output, while the variables of seeds, pesticides, and labor did not have a significant effect on output. Urea and NPK fertilizers were found to increase production variability and thus significantly increased production risk in lowland rice farming. Meanwhile, seeds, pesticides, and labor increased production risk insignificantly. The expansion of land area tended to reduce production risk, although the effect was not statistically significant. The average value of technical efficiency in the use of production inputs in the research area was considered technically efficient (TE > 0.70).